Stray animals awareness campaign for SSPCA in Kuching - Angelia, Lock (Universiti Malaysia Sarawak (UNIMAS), 2015)
In Malaysia, the crisis of stray overpopulation is getting more and more serious. Due to the lack of awareness and social concern towards the crisis in the local society and many other factors, this social issue is often being neglected. Many other countries such as Singapore, Hong Kong and the United States of America have already started to take serious efforts in solving this problem and there are successful results to prove that the problem is solvable if the awareness towards the issue is educated among the people. However, Malaysia is still at the beginning stage of saving the poor strays and there is a lack of visual elements that could help in creating the awareness among the society. Therefore, the aim of this project is to propose an awareness campaign that implements the advertising techniques of Direct Marketing that could help the Sarawak Society for the Prevention of Cruelty to Animals (SSPCA) in raising awareness, changing public attitudes and behaviour towards the issue of stray animals.